Seeking feasible reconciliation: A transdisciplinary contextual approach to reconciliation - Thesnaar, Christoffel H. (HTS teologiese studies, 2014)
In South Africa scholars in the broad field of practical theology are currently faced with a daunting challenge: to rethink the reconciling role of the institutional church in the light of continued challenges facing reconciliation within post-apartheid and post-Truth and Reconciliation Commission (TRC) South Africa. This contribution investigates whether the transdisciplinary, region-centred scientific research approach with a focus on the Hölderlin perspective on reconciliation could assist scholars in practical theology to address reconciliation in a post-apartheid and post-TRC society. The article proposes a contextual and constructive approach to reconciliation in order to assist South African scholars in the field of practical theology and the institutional church to address the challenges of reconciliation in a post-apartheid and post-TRC society. The contribution confirms that this approach does indeed assist the field of practical theology to contribute to reconciliation without the risk of speaking a language that nobody beyond theology can understand.